Orientation Towards Agile Leadership for Coaches to Enhance the Culture of Entrepreneurship Among Business Incubator’s Students at Laghouat University. - Hadjer Linani; Hassina Kadira Toumi (Dirassat Journal Economic Issue, 2025)
This study aimed to define the extent to which coaches are characterized with agile leadership and their impact in enhancing the entrepreneurship culture among business incubator's students at Laghouat University. To achieve the study objectives, a questionnaire was designed to collect data the study sample, which was 60% out of 60 students of the business incubator at Laghouat University, which presented in 36 students. The method used was the structural equations modeling by Smart-pls 4 software and SPSS 23. Findings indicate that there is no direct impact for agile leadership in enhancing the entrepreneurship culture among business incubator's students at Laghouat University. Also, there is no direct impact of the dimensions of agile leadership (humbleness, tranquility, wisdom and objectivity, patience, and trust) in enhancing the entrepreneurship culture among students. Thus, there are no differences in the impact of agile leadership in enhancing the entrepreneurial culture among students due to (Gender, age and educational level).